Management in wartime (Ukrainian businesses) - Efros, Kateryna (2024)
This master's thesis explores the management strategies, employee well-being practices, and organizational resilience of Ukrainian businesses operating during wartime. By combining theoretical foundations with practical insights from interviews with CEOs and managers from various industries, the study provides a comprehensive understanding of the challenges faced by these companies and the adaptations they have made to navigate the complexities of the conflict. The research highlights the importance of effective leadership, communication, and collaboration in guiding businesses through the crisis, as well as the critical role of employee safety, well-being, and productivity in maintaining organizational resilience. The findings contribute to the existing knowledge on management practices during wartime and offer valuable lessons for businesses operating in conflict-affected regions, emphasizing the need for adaptability, innovation, and a forward-looking approach to recovery and growth in the post-war period.